Recidivists Convicted in Poland in the Transition Period, in the Light of Statistical Data (Archives of Criminology, 2008)
The issues presented in the article concern criminal and penitentiary recidivism. The author points out the most groundbreaking and noteworthy changes related to the normalization of recidivism, which were introduced to the penal law in the first period of transformation. The article describes, in particular, the optional aggravation of punishment or the introduction of a new condition that may aggravate criminal responsibility in the case of acts of significant social harm, i.e. aggressive crimes. Apart from these differences, the other consequences of recidivism are also regulated differently. The author also gives a definition of penitentiary recidivism, which was only introduced to the Penal Code in 1997. The text mainly details the in-depth comparative analysis referring to recidivism in the light of statistics from the Ministry of Justice on convictions before and after the transformation. In summary, Teodor Szymanowski refers to the changes in the criminal liability of recidivists, especially in the context of the penalties administered to them, including mitigating penalties and waiving additional rehabilitation measures, as well as defining a new profile of recidivists and the crime that is characteristic for them.